Progressive Trends in Electronic Resources Management Among Academic Libraries in Hong Kong. Issue 3 (2nd April 2017) - Lo, Patrick; Cho, Allan; Law, Belle Kun-Kei; Chiu, Dickson K. W.; Allard, Bradley
ABSTRACT: Due to recent technology advancement and particularly ubiquity of smart devices, user needs and habits of using library materials are also changed towards electronic resources, which facilitate anytime anyplace access as well as easier information search. For library management, digital resources facilitate long-term preservation together with savings of space and human costs. This lead to a trend of rapid development of digitization and electronic resources, leading to lots of changes in academic libraries. However, there are few studies providing a holistic view of this important trend, especially in metropolis of the East. To explore this trend, we interviewed four librarians in different departments from different universities in Hong Kong for a qualitative analysis on various aspects such as digital versus print, user expectation changes, and new management problems. Emerging issues of e-resources highlighted by the libraries includes acquisitions policies, budget implication, copyright, and access restrictions, consortium collaboration, manpower issues, workflow, and library system changes. We further discuss the practical implications of our findings, which are supportive to those disparate in other literature.